Lebanese building law between texts, Application gaps and land scarcity (Journal of Planner and Development, 2023)
This paper examines the gaps in Lebanese building law as well as the exploitation of contractors, stakeholders, and residents in order to make illegal profits at the expense of The Shape of urban agglomerations and their expansion in cities and rural areas, which is contrary to the principles of sustainable land development. It also emphasizes the amplification of the factors of vertical and horizontal building investments in the implementation of buildings contrary to the license, as well as the burden that this places on the city’s resulting infrastructure and ability to absorb the activities and needs of its residents. The study then presents recommendations in the process of transformation in the technique of planning and application based on the environmental and economic hazards of this current situation.